(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: describe the process of implementing the Rede de Atenção à Saúde em Lesões Cutâneas (Health Care Network for Skin Injuries) in the municipality of Divinópolis - MG. Method: it is an experience report on the implementation of a Health Care Network for Skin Injuries from the Programa de Educação Pelo Trabalho para Saúde (PET-Saúde/GraduaSUS) (Education Through Work for Health Program), from May 2016 to April 2018. Teachers and students from a public university and professional nurses linked to the Municipal Health Secretariat of the municipality participated in the actions. Results: it was possible to implement the Health Care Network for the prevention and treatment of skin lesions in a structured and systematic way. A flow of care, case supervision and clinical follow-up was established through the construction of an assistance protocol. Conclusion: the practical skill and scientific knowledge of students and health professionals for the treatment and management of skin lesions were developed, thus strengthening the teaching-service-community triad.